Dietary patterns and risk of colorectal adenoma: a systematic review and meta‐analysis of observational studies. Issue 6 (14th July 2016) - Godos, J.; Bella, F.; Torrisi, A.; Sciacca, S.; Galvano, F.; Grosso, G.
Abstract: Background: Current evidence suggests that dietary patterns may play an important role in colorectal cancer risk. The present study aimed to perform a systematic review and meta‐analysis of observational studies exploring the association between dietary patterns and colorectal adenomas (a precancerous condition). Methods: Pubmed and EMBASE electronic databases were systematically searched to retrieve eligible studies. Only studies exploring the risk or association with colorectal adenomas for the highest versus lowest category of exposure to a posteriori dietary patterns were included in the quantitative analysis. Random‐effects models were applied to calculate relative risks (RRs) of colorectal adenomas for high adherence to healthy or unhealthy dietary patterns. Statistical heterogeneity and publication bias were explored. Results: Twelve studies were reviewed. Three studies explored a priori dietary patterns using scores identifying adherence to the Mediterranean, Paleolithic and Dietary Approaches to Stop Hypertension (DASH) diet and reported an association with decreased colorectal adenoma risk. Two studies tested the association with colorectal adenomas between a posteriori dietary patterns showing lower odds of disease related to plant‐based compared to meat‐based dietary patterns. Seven studies identified 23 a posteriori dietary patterns and the analysis revealed that higher adherence to healthy and unhealthy dietary patterns was significantly associated risk of colorectal adenomas (RR = 0.81, 95% confidence interval = 0.71, 0.94 and RR = 1.24, 95% confidence interval = 1.13, 1.35, respectively) with no evidence of heterogeneity or publication bias. Conclusions: The results of this systematic review and meta‐analysis indicate that dietary patterns may be associated with the risk of colorectal adenomas.